Re-hospitalisation after transcatheter aortic valve implantation: the HOSPITAVI study. (3rd October 2022) - Baekke, P; Joergensen, T H; De Backer, O; Sondergaard, L
Abstract: Background: Previous studies have shown increased re-hospitalisation rates for patients treated with transcatheter aortic valve implantation (TAVI) within the first post-procedural year. Most of these may be due to pre-existing co-morbidities, periprocedural complications, or suboptimal post-discharge plan. However, data on re-hospitalisation causes and associations with the TAVI procedure are limited. Purpose: The aims of this study were to assess the incidence and cause of re-hospitalisation in patients with severe, symptomatic aortic stenosis treated with TAVI. Methods: All patients who underwent TAVI at our centre between 2016 and 2020 were followed at patient-level during the first year after index admission. The risk of re-hospitalisation was calculated after discharge from index admission. All patients' medical records were reviewed to validate the cause of re-hospitalisation and mortality according to The Valve Academic Research Consortium 3 definitions. Results: In total, 1, 482 consecutive patients had undergone TAVI from 2016 to 2020, of whom 79 patients were excluded due to aortic regurgitation, conversion to surgical aortic valve replacement during index admission or residing abroad. Thus, the total study population consisted of 1, 403 patients with a median age of 80 years (IQR: 75–84 years). Median length of stay for the post-procedural index admission was 2 days (IQR: 1–3 days). The total rate of all-cause re-hospitalisation per 100 patient years was 2.7 within the first 30 days, 1.1 from day 31 to 90, and 0.8 from day 91 to the first-year post-discharge. Within the first post-discharge year, 48.6% of the patients were re-hospitalized at least once, of which 26.2% (CI: 23.9–28.5%) of the first re-hospitalisations were of cardiovascular cause compared to 22.4% (CI: 20.2–24.6%) of non-cardiovascular cause. Median length of stay for the first re-hospitalisation was 3 days (IQR: 2–7 days). The most common cardiovascular causes were arrhythmias (28.1% of which 40.6% led to permanent pacemaker implantation), heart failure (14.4%), and neurological events (14.4%). The most common non-cardiovascular causes were infectious diseases (18.3% with pneumonia accounting for 40.4% of these admissions). The first re-hospitalisation was elective in 14.8% of the admissions, primarily due to percutaneous left atrial appendage closure, cancer, or osteoarthritis. Conclusion: Almost half of the patients treated with TAVI between 2016 and 2020 were re-hospitalized within the first year after the index admission. First post-procedural re-hospitalisation was more often due to cardiovascular than non-cardiovascular cause with arrhythmias accounting for approximately 30% of cardiovascular re-hospitalisations. Further work is needed to explore whether the rate and causes of hospitalisations differ in the general population and to potentially establish a risk model to predict patients at high-risk of re-hospitalisation. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Boston ScientificAbbott